Use of peripheral electrical stimulation on healthy individual and patients after stroke and its effects on the somatosensory evoked potentials. A systematic review - Mijic, Marko; Jung, Andres; Schoser, Benedikt; Young, Peter (Frontiers in Neurology, 2022)
Introduction: A few studies have used somatosensory evoked potentials (SEP) to demonstrate sensory changes and cortical plasticity among healthy subjects or to estimate the rehabilitation prognosis after intervention with peripheral electrical stimulation (PES) by stroke patients. Our primary aim was to systematically review whether PES has a role in changing latencies and amplitudes of SEPs in healthy subjects and stroke patients. We searched for a correlation between sensory and motor function assessments and changes in SEP components. Methods: The following databases were searched: Pubmed/MEDLINE, Scopus/ScienceDirect, Web of Science/Clarivate, Cochrane Library, The Physiotherapy Evidence Database (PEDro), and ClinicalTrials.gov. Titles and abstracts, as well as full-text reports, were screened for eligibility by two independent reviewers according to priori-defined eligibility criteria. There were no study limitations concerning the treatment of the upper limb, lower limb, or torso with PES. Results: The systematic search resulted in 11344 records, however only 10 reached the quality level for the final evaluation. We could not find enough evidence to confirm the use of SEP as a predictor to estimate the rehabilitation prognosis after stroke. However, we found a correlation between different sensory and motor function assessments and changes in SEP components. The stroke studies involving PES that initiate a voluntary contraction used for a specific movement or task indicate a positive relationship and correlation to assessments of motor function. Discussion: We found that PES have predicting impact of sensory brain reorganization as mirrored by change in SEP amplitude and latency. In order to confirm this hypothesis, we suggest conducting a randomized controlled study on healthy subjects and stroke patients.